Education on preventing the spread of covid-19 to traders at the Museum Manusia Purba Sangiran - Purnamarini, Tri Ratna; Wiranto, Dody (Community Empowerment, 2021)
The Museum Manusia Purba Sangiran has been temporarily closed since March 15, 2020 due to Covid-19 and only reopened on April 10, 2021. With the reopening of the Museum Manusia Purba Sangiran to the public, it has the potential to create a new cluster in the transmission of Covid-19. Therefore, this service activity was intended as a form of effort to prevent the transmission of the Covid-19 virus among traders in the tourist area of the Sangiran Ancient Human Museum. The activities carried out were the installation of educational banners to always wear masks, maintain distance, wash hands and stay at home. Other activities that were also carried out were the distribution of masks and hand sanitizers. The results obtained were an increase in public awareness to take better care of themselves and be aware of the dangers of the Covid-19 virus, by getting used to always using masks, diligently washing hands or cleaning hands with hand sanitizers and always keeping a distance.